Improved direct field oriented control of multiphase induction motor used in hybrid electric vehicle application. (27th July 2017) - Iffouzar, Koussaila; Amrouche, Bessam; Otmane Cherif, Tahar; Benkhoris, Mohamed-Fouad; Aouzellag, Djamal; Ghedamsi, Kaci
Abstract: This paper presents an improved direct rotor field oriented control of seven phase induction motor in hybrid electric vehicle (HEV) system. The dynamic model of the machine shows that non-sequential currents producing no torque appear and degrade the quality of currents. Further, the fuzzy logic controller is proposed to filter non-sequential components and improves the quality energy. Hybridization of the electric vehicle by a fuel cell (HEV) and an auxiliary energy source has the advantage of improving the dynamic response and efficiency of the system. Indeed, an ultra-capacitor (UC) used as a means of energy storage to enable the lower dynamic FC when changes in power fast and recovers braking energy as well as absorption of immanent disturbances of the static converters. Improving the quality of energy demand can improve not only the lifetime of the actuator but also the onboard sources. One of the results of the reduction of interference in the system induces to the reduction of mechanical vibrations, which generates quieter systems, which is an advantage for these urban transport applications. In this paper, the modeling of the different parts of the multi-physical system that represent hybrid vehicle are presented. The performance of the aimed system is analysed under different acting conditions. Highlights: New control of seven-phase induction machine using fuzzy logic filter. Improvement of the quality of the power to demand of HEV. Improvement of the lifetime of the HEV on-board sources. A discrete system and a better comfort are obtained with this application.